Child and caregiver reported problems in using asthma medications and question‐asking during paediatric asthma visits. (29th May 2013) - Sleath, Betsy; Carpenter, Delesha M.; Beard, Ashley; Gillette, Christopher; Williams, Dennis; Tudor, Gail; Ayala, Guadalupe X.
Abstract Objectives The objectives of the study were to describe the extent to which lay caregivers and children who reported asthma medication problems asked medication questions during their medical visits. Methods Children with asthma ages 8 through 16 years and their caregivers were recruited at five paediatric practices and their medical visits were audiotape recorded. Children were interviewed after their medical visits and caregivers completed questionnaires. A home visit was conducted 1 month later. Generalized estimating equations were used to analyse the data. Key findings Two hundred and ninety six families participated. Among those caregivers who reported asthma medication problems, only 35% had asked at least one medication question during the visit. Among children who reported asthma medication problems, only 11% had asked at least one medication question during their consultation. Caregivers and children who reported a problem with their asthma medications were significantly more likely to have asked medication questions if providers had asked more questions about control medications. Children who reported higher asthma management self‐efficacy were significantly more likely to have asked an asthma medication question. Conclusions Only one in three caregivers and one in 10 children who reported an asthma medication problem asked a question during their medical visits and many still reported these problems 1 month later. Pharmacists should encourage caregivers and children to report problems they may be having using their asthma medications.